The Role of Problem Solving Approach on Student’s Mathematical Critical Thinking Ability and Disposition - Asep Mulyana; Utari Sumarmo; Rudi Kurniawan ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This study was a pre test-post test experimental control group design having a goal to analyze  the role of prior mathematics ability (PMA) and Problem Solving Approach (PSA) on student’s mathematical critical  thinking ability (MCTA)  and disposition (MCTD). The study involved 65  eleventh grade students, a prior mathematics ability (PMA), a MCTA test, a  MCTD scale. The study found that PMA and PSA took roles on obtaining student’s MCTA and MCTD, those were the higher student’s PMA the study found the higher students MCTA and MCTD. Beside that, on MCTA and its N Gain, entirely and with low and medium PMA students  getting treatment with PSA attained  better grades than the grades of students taught by conventional teaching (CT);  and for entirely and with medium and high PMA, student recieving treatment with PSA obtained higher grades on MCTA and MCTD than student  taught by CT and those grades were at good grade level. The other findings, there was no association between MCTA and MCTD, and no interaction between PAM and teaching approaches toward MCTA and on MCTD and student  learn  actively during PSA